Are infection specialists recommending short antibiotic treatment durations? An ESCMID international cross-sectional survey. (16th January 2018) - Macheda, Gabriel; Dyar, Oliver J; Luc, Amandine; Beovic, Bojana; Béraud, Guillaume; Castan, Bernard; Gauzit, Rémy; Lesprit, Philippe; Tattevin, Pierre; Thilly, Nathalie; Pulcini, Céline; ,
Abstract: Objectives: To evaluate the current practice and the willingness to shorten the duration of antibiotic therapy among infection specialists. Methods: Infection specialists giving at least weekly advice on antibiotic prescriptions were invited to participate in an online cross-sectional survey between September and December 2016. The questionnaire included 15 clinical vignettes corresponding to common clinical cases with favourable outcomes; part A asked about the antibiotic treatment duration they would usually advise to prescribers and part B asked about the shortest duration they were willing to recommend. Results: We included 866 participants, mostly clinical microbiologists (22.8%, 197/863) or infectious diseases specialists (58.7%, 507/863), members of an antibiotic stewardship team in 73% (624/854) of the cases, coming from 58 countries on all continents. Thirty-six percent of participants (271/749) already advised short durations of antibiotic therapy (compared with the literature) to prescribers for more than half of the vignettes and 47% (312/662) chose shorter durations in part B compared with part A for more than half of the vignettes. Twenty-two percent (192/861) of the participants declared that their regional/national guidelines expressed durations of antibiotic therapy for a specific clinical situation as a fixed duration as opposed to a range and in the multivariable analysis this was associated with respondents advising short durations for more than half of the vignettes (adjusted OR 1.5, P  =   0.02). Conclusions: The majority of infection specialists currently do not advise the shortest possible duration of antibiotic therapy to prescribers. Promoting short durations among these experts is urgently needed.